Preventing Acute Kidney Injury and Hypotension After Elective Total Joint Arthroplasty Is Possible: An Update to an Established Multidisciplinary Protocol. Issue 24 (15th December 2021) - Malige, Ajith; Carmona, Aldo; Roscher, Christopher; Herman, Daniel; Filipkowski, Amy; Rowbotham, Jaclyn; Sgro, Jessica; Gould, William; DeLong, William; Gayner, Robert
Abstract : Introduction: Based on preoperative and perioperative risk factors that have been found to correlate with the development of acute kidney injury (AKI), our institution developed a protocol aimed at managing and improving outcomes in all elective THA and TKA patients. This article highlights the continued success and growth of our protocol aimed at decreasing AKI and hypotension in elective total joint arthroplasty patients. Method: A multidisciplinary team comprising orthopaedic surgeons, nephrologists, anesthesiologists, cardiologists, and internal medicine hospitalists created a comprehensive protocol aimed at decreasing complications after elective joint arthroplasty and improving clinical outcomes across multiple hospitals. Patient demographics, hospital length of stay, readmission rates, mortality, and postoperative AKI and hypotension incidences were recorded and compared between preprotocol phase I (initial protocol implementation) and phase II (protocol expansion across 10 hospitals) patient cohorts. Results: Overall, 3, 222 patients over 56 months and 10 hospitals were included. Our phase II AKI rate (0.6%) was significantly lower than our preprotocol rate (6.2%, P < 0.01) and statistically similar to our phase I rate (1.2%, P = 0.61). Our hypotension rate in phase II (6.8%) was significantly lower than our preprotocol rate (12.7%, P < 0.01) but statistically similar to our phase I rate (5.9%, P = 0.40). Furthermore, a significant decrease was observed in hospital length of stay ( P < 0.01) over time, but no difference was observed in readmission ( P = 0.59) and mortality rates ( P = 1.00) over time. Discussion: This protocol-driven interventional study provides a detailed and successful multidisciplinary method to manage and decrease rates of AKI and hypotension in a large patient cohort across multiple hospital centers.